Development a novel paradigm for characterization of emerging contaminants in mixed-use anthropogenic impacted watersheds - Lee, Theodora Hui Yian (Nanyang Technological University, 2024)
There are more than 100,000 compounds used in daily applications and approximately 65 million chemicals formulated for commercial use. Within the group of compounds are emerging contaminants of concern, which are either newly introduced or have new scientific evidence of detrimental harm to human health and or the environment. In addition, during disinfection of water, these compounds are often transformed into other compounds that may be more or less toxic than the starting chemical. This results in a prioritization dilemma when selecting contaminants for water quality monitoring. Emerging contaminants are found ubiquitously in all environmental matrices including surface water, groundwater and sediment, suggesting their propensity to be transported over large distances and persistent in the environment due to continuous input from anthropogenic sources. Moreover, Southeast Asia is a region especially vulnerable to emerging contaminant pollution given their high reliance on groundwater resources, rapid population growth, poor sanitation systems in peri-urban areas and agriculture expansion coupled with pesticide overuse. Despite the urgent need for emerging contaminant monitoring in this region, high infrastructural costs, complicated analytical methods, labour intensive requirements are barriers to implement regular water quality monitoring of emerging contaminants. To address these issues, this thesis aimed to develop a novel paradigm for the characterization of emerging contaminants in a mixed-use anthropogenic impacted watershed. This thesis first investigated the influence of the built environment on emerging contaminant distribution and prevalence, comparing between urban areas, agriculture, rural, remote areas, and subsurface water. Next, this thesis focused on target analysis, non-target screening and in vitro bioassay techniques, evaluating their utility for characteriation and water quality monitoring in a mixed-use watershed based on these criteria: sensitivity, selectivity, specificity, scope, transferability and practicality. As current monitoring methods are extremely resource intensive, this research will evaluate the effect-based monitoring technique which was designed to have a more cost-efficient and systematic approach in utilizing state-of-the-art analytical techniques. The last key chapter of this thesis focused on the use of an environmental surrogate, fluorescence EEM. Environmental surrogates thus offer a rapid and lower cost solution for emerging contaminant monitoring. With more compounds synthesized overtime, it is nearly impossible to monitor all compounds. Thus, the understanding of spatial and temporal variations of contaminant source and sink becomes a priority in contaminant research to aid intervention. This thesis aimed to characterize sources of contaminants from different land use types – e.g. wastewater treatment plants, urbanized, peri-urbanized or from agriculture areas, in surface water and groundwater profiles using fluorescence EEM. Applications of identifying suitable environmental surrogates will allow for rapid intervention in identifying the sources of contamination and also enable long-term monitoring of emerging contaminants in this highly understudied region.